Uma análise aos fluxos migratórios e dinâmicas do deslocamento forçado na Colômbia para o período 2000-2007 - Karo Ramírez Duque (Confins)
One of the main consequences generated by the armed conflict in Colombia is the internal displacement. Analyze the social impacts of a conflict that has persisted for over fifty years is especially relevant because it directly affects the civilian population, victims of violence. Therefore, this article aims to analyze the spatial dynamics of migration of forced displacement exploring the problem from the field of geography and cartography. In Colombia, the 2000s was marked by the resurgence of armed conflict that left a balance of more than four million people displaced and at least 260,000 dead according to the Red Nacional de Información (RNI for its Spanish acronym), of the Government of Colombia. Thus, this article aims to analyze the forced displacement for the first seven years of the 2000s, owing to the fact that in 2007 was the last peak of forced displacement in the country.